Atrial fibrillation substrate mapping with decrement evoked potential mapping. (24th May 2021) - Salvador-Montanes, O; Fitzgerald, J; Jackson, N; Haldar, S; Cotton, J; Gizurarson, S; Nanthakumar, K; Porta-Sanchez, A
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Sociedad Española de Cardiologia. OnBehalf: DEFINE-AF Background: Identifying and targeting atrial substrate zones that are vulnerable to unidirectional block and slow conduction may be critical to improve the outcomes of atrial fibrillation (AF) ablation. Functional mapping of the atrial substrate with Decrement Evoked Potential (DeEP) and a single extrastimulus in this population could potentially lead to novel therapeutic strategies. Aim: 1) To systematically analyze whether the DEEP are present in the atrial tissue and their locations after pulmonary vein isolation. 2) To assess their relationship with the underlying voltage. 3) To assess the presence of DEEP as a function of the subtype of AF. Methods: Consecutive patients with AF undergoing ablation were prospectively enrolled at 3 institutions. A biatrial voltage map was created and after pulmonary vein isolation (PVI). A drive train and an extrastimulus (atrial refractory period + 20ms) was delivered from an epicardial site (proximal CS) and an endocardial site (left atrial appendage (LAA). A multipolar mapping catheter was sequentially placed at 8 left atrial sites and 5 right atrial sites. Electrograms (EGMs) that showed a local delay of >10ms in activation with the extrastimulus were identified as DEEPs. Patients were followed for a mean of 11 ± 5 months Results: 74 patients, 63 pers AF (85%), mean age 62 ± 8, mean LA size 41 ±12 mm were enrolled. Of 19240 EGMs analyzed, 8.2% showed DEEPs (54.6% with CS pacing and 45.4% with LAA pacing, p = 0.0001). The mean local decrement seen was 39 ms. Most DEEPs (76.2%) were identified in sites with a normal EGM at baseline with preserved voltages. DEEPs were differentially distributed within the regions mapped, more frequently in LA than RA (9.2% vs 6.6%, p < 0.0001). Patients with persistent AF had a higher proportion of DEEPs than patients with paroxysmal AF (9.7% vs 5.1%, p < 0.001). Conclusions: Atrial DEEPs are: 1) More often identified when pacing endocardially. 2) More common in patients with persistent AF. 3) More frequent in the LA than in the RA. 4) Mostly located in regions with normal voltages at baseline. All those findings suggest the importance of the functional substrate mapping in the atrium and could lead to novel therapeutic targets.